1954
DOI: 10.2118/410-g
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bubble Formation in Oil Recovery by Solution Gas Drives in Limestones

Abstract: Laboratory data show that the gas-oil ratio performance of non-uniform porosity limestones produced by solution gas drive is sensitive to producing rate and to fluid properties. Non-uniform porosity limestones are those for which laboratory solution and external gas drive tests yield considerably different relative permeability ratio characteristics.The oil recovery performance by solution gas drive depends directly on the number of gas bubbles formed. Laboratory rates of pressure decline, which are 100 to 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 1 publication
2
14
0
Order By: Relevance
“…This finding has been reported by several researchers. 2,6,21 As shown in Table 3 and 4, some of the slow tests (e.g. run 3) exhibit supersaturation values (and pressure-decline rates) that are similar to those observed in some of the fast experiments (e.g.…”
Section: Average Sand-pack Pressuresupporting
confidence: 60%
See 1 more Smart Citation
“…This finding has been reported by several researchers. 2,6,21 As shown in Table 3 and 4, some of the slow tests (e.g. run 3) exhibit supersaturation values (and pressure-decline rates) that are similar to those observed in some of the fast experiments (e.g.…”
Section: Average Sand-pack Pressuresupporting
confidence: 60%
“…Several researchers 6,7,8,9,10,11,12 reported that at high pressure decline rates more bubbles are formed because the higher pressure decline rate results in greater supersaturation and nucleation rate. Firoozabadi 13 concluded that high rates of pressure decline could activate a large number of nucleation sites and therefore the critical gas saturation can be two to five times higher than the values at low dp/dt.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers (Stewart et al 1954;Hunt and Berry 1956;Handy 1958;Danesh et al 1987;Moulu 1989;Bora et al 1997;Maini 2003) reported that at high pressure-decline rates more bubbles are formed because the higher pressure-decline rate results in greater supersaturation and nucleation rate. Firoozabadi (2001) concluded that high rates of pressure decline could activate a large number of nucleation sites, and, therefore, the critical gas saturation can be two to five times higher than the values at low dp/dt.…”
Section: Introductionmentioning
confidence: 99%
“….. ,,,.,,, .,,,.~, -,~,~.$.T-Y-.7--.,, , -----hours waiting. Stewart et al (1953Stewart et al ( , 1954) perform a systematic study of the role of supersaturation in oil recovery by solution gas drive in limestone. The supersaturation obtained was more than 20 psi at 10 psi/day pressure drawdown.…”
Section: -9mentioning
confidence: 99%